Melting dynamics of Gold thin film: A Molecular Dynamics study. Issue 6 (March 2021) - Fahdiran, R; Handoko, E; Sugihartono, I; Budi, S
Abstract: We studied the melting dynamics of Gold in the form of thin film. The thin film thickness is 9.756 nm. The systems are heated from room temperature up to slightly above melting point, Tm = 1338 K. The evolution of the atoms in each system is followed using Molecular Dynamics (MD) scheme up to 20 ps. Thermodynamics analysis indicated that thin film is suppressed by the uniform heat while the temperature is increasing. Structural analysis compared with Common Neighbor Analysis (CNA) expressed the condition that melting conduction occurred at the end of simulation.